Inhibition of 5-alpha-reductase activity induces stromal remodeling and smooth muscle de-differentiation in adult gerbil ventral prostate - Corradi, L. S.; Carvalho, H. F.; Goes, R. M.; Taboga, SR (Blackwell Verlag Gmbh, 2004)
Prostatic differentiation during embryogenesis and its further homeostatic state maintenance during adult life depend on androgens. Dihydrotestosterone, which is synthesized from testosterone by 5alpha-reductase (5alpha-r), is the active molecule triggering androgen action within the prostate. In the present work, we examined the effects of 5alpha-reductase inhibition by finasteride in the ventral prostate (VP) of the adult gerbil, employing histochemical and electron microscopy techniques to demonstrate the morphological and organizational changes of the organ. After 10 days of finasteride treatment at a dose of 100 mg/kg/day, the prostatic complex (VP and dorsolateral prostate) absolute weight was reduced to about 18%. The epithelial cells became short and cuboidal, with less secretory blebs and reduced acid phosphatase activity. The luminal sectional area diminished, suggestive of decreased secretory activity. The stromal/epithelial ratio increased, the stroma becoming thicker but less cellular. There was a striking accumulation of collagen fibrils, which was accompanied by an increase in deposits of amorphous granular material adjacent to the basal lamina and in the clefts between smooth muscle cells (SMC). Additionally, the periacinar smooth muscle became loosely packed. Some SMC were atrophic and showed a denser array of the cytoskeleton, whereas other SMC had a highly irregular outline with numerous spine-like projections. The present data indicate that 5alpha-r inhibition causes epithelial and stromal changes by affecting intra-prostatic hormone levels. These alterations are probably the result of an imbalance of the homeostatic interaction between the epithelium and the underlying stroma.
Keywords: prostate; 5 alpha-reductase; finasteride; stromal reorganization; smooth muscle de-differentiation